Dobiášová versus Tučková. On novels thematizing the search for (female) spirituality - Lollok, Marek (Bohemica Olomucensia, 2023)
The paper deals with the newest novels by Tereza Dobiášová (Tajemství. Neskutečný příběh Anežky České [Secret. The Unreal Story of Agnes of Bohemia]) and Kateřina Tučková (Bílá Voda). Both of these works concern, among other things, the search for feminine spirituality as well as the most famous Czech saint Anežka Česká; both are set in the Czech past (the former is set in the Middle Ages, the latter predominantly in the second half of the 20th century). The paper compares these novels and monitors similarities and differences (such as different story-construction, plot centres, focuses and goals, etc.). It also notes the similar motivation of the authors (spiritual quest), as well as their constant interest in the issue of the women's position in the contemporary society and particularly in the (Catholic) Church.
Keywords: Contemporary Czech prose; novel; Tereza Dobiášová; Kateřina Tučková